Efektivitas Advokat sebagai Mediator - Zulfikri Zulfikri; Alif Randi Ramadhan; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Mediation is an initial step in the court process. This step is taken before entering into the trial process. In the mediation process it is hoped that both parties can reconcile with each other in their case. so that the mediation process is increasingly encouraged so that it can accelerate the process of resolving a dispute. In the mediation process, of course, the role of the mediator is the key to the success of mediation. Experienced mediators can of course bring together the two parties who are in dispute and reconcile it. Mediators themselves are not only limited to the court environment. However, mediators from outside the scope of the court also have a strategic role in the mediation process. An advocate is considered to have good skills in carrying out this mediation process, because an advocate has a deeper relationship with his clients. It is hoped that the inclusion of an advocate as a mediator can actually resolve the problem without any party feeling disadvantaged and the results of the mediation can be better understood by the litigants. Keywords: Advocate, law and Legal Profession